A Unified Cloud Platform for Autonomous Driving. - Liu, Shaoshan; Tang, Jie; Wang, Chao; Wang, Quan; Gaudiot, Jean-Luc (Computer (00189162), 2017)
Tailoring cloud support for each autonomous-driving application would require maintaining multiple infrastructures, potentially resulting in low resource utilization, low performance, and high management overhead. To address this problem, the authors present a unified cloud infrastructure with Spark for distributed computing, Alluxio for distributed storage, and OpenCL to exploit heterogeneous computing resources for enhanced performance and energy efficiency.